Do large companies have better environmental performance? Evidence from Chinese listed companies - Liang, Yiming; Wu, Rui (Frontiers in Sustainability, 2026)
IntroductionIn the context of global advocacy of sustainable development, the environmental, social and governance (ESG) performance of firms, as an important indicator for measuring the sustainability of corporate development, has been widely used in the process of corporate management decision-making and financial market investment. Thus, examining the influence of firm size, a key factor, on ESG performance is essential for driving corporate sustainability. Large companies have longer-term development goals and greater social responsibility, often placing greater emphasis on environmental issues. On the other hand, large companies face more difficult management problems than small companies, e.g., coordination between superiors and subordinates, coordination between departments. Thus, the low efficient coordination will affect environmental performance of large companies.MethodsThis study investigates the relationship between Environmental, Social, and Governance (ESG) performance and firm size using a sample of Chinese A-share listed companies from 2012 to 2021. Firm size is proxied by total assets, the number of employees, and operating revenue.ResultsThe results show that ESG performance is positively correlated with firm size. The correlation coefficients between asset, employee, revenue and ESG are 0.253, 0.268, and 0.200, respectively. The results are robust for different nature of ownership and pollution.DiscussionThe study suggests that governments and investors should consider the different ESG capacity between large and small companies to make fair decisions.